Chronisch obstruktive Lungenerkrankung mit periorbitaler und subkonjunktivaler Schwellung = Chronic obstructive pulmonary disease, periorbital and subconjunctival swelling - Rivinius, Rasmus; Futterer, Simon; Puderbach, Michael; Herth, Felix; Heußel, Claus Peter (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2012)
A 70-year-old man with a history of chronic obstructive pulmonary disease (COPD) and dilative cardiomyopathy was referred due to acute dyspnea and chest pain. After spontaneous pneumothorax was confirmed by chest radiography, a chest tube was inserted into the right side. Persistent air bubbles escaping through the water seal of the drainage in synchrony with respiration indicated a bronchopleural fistula. A physical examination revealed orbital and subconjunctival emphysemas. Skull and chest computed tomography (CT) scans showed further massive cervical, thoracic and pulmonary subcutaneous emphysemas which are increased subcutaneous amounts of gas which can disperse along the fasciae. Cardinal sign is the sensation of air under the skin known as subcutaneous crepitation (similiar to touching rice crispies). Conditions causing subcutaneous emphysemas are trauma, medical treatment and intracutaneous gas production by bacteria. In this case, large amounts of air leaked out of the pleural space through the incision made for the chest tube into the subcutaneous tissue, mediastinum and retroperitoneum causing subcutaneous emphysemas. From there, ascending air spread along the fascial planes of the mediastinum and cervical area through the inferior orbital fissure to the orbits and eyelids causing orbital and subconjunctival emphysemas. On the basis of the progressive emphysemas and persistent pneumothorax, a second chest tube was inserted. Subsequently, the signs and symptoms disappeared completely.